INFLUÊNCIA DE DIFERENTES TRANSLUCIDEZ DAS CERÂMICAS SOBRE O GRAU DE CONVERSÃO E MICRODUREZA DE UM CIMENTO RESINOSO DUAL - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
The proposition of this study was to evaluate the influence of different ceramic translucency on the degree of conversion and Knoop microhardness of dual resin cement. It was made 150 samples of the resin cement dual cured Variolink II (shade A3; 5 mm in diameter and 1 mm thick) were created with interposing ceramic discs with 8 mm in diameter and 1.5 mm thick varying translucency (IPS e.max HT, HO, ZirPress HT and IPS d.SIGN). The control group was created without the interposition of ceramics. The experimental groups were photoactivated in three different times: 20, 40 and 60 seconds. 75 specimens were measured by Fourier transformed infrared spectroscopy (FTIR) to assess the degree of conversion (%). Another 75 specimens were used for the microhardness test, previously they were ground under water irrigation with grit silicon carbide granulation 320, 400, 600, 1000, 1200, finishing them with felt cloth and diamond paste with grain 1 and ¼ micrometers. Each sample was divided into four quadrants and conducted an indentation in each quadrant and then was calculated the average of these indentations. The values of the degree of conversion and Knoop hardness were analized by two-way ANOVA (type of ceramic and time of photoactivation), Bonferroni’s multiple comparison tests with a significance level of 5% and the Spearman correlation. The degree of conversion values of ceramic with high translucency were similar to the control group, the HO group presented the lowest conversion values, however when the curing time has tripled from 20 to 60 seconds, the values increased 63.9%. Translucent ceramic without infrastructure (IPS d.SIGN) presented higher microhardness values than ceramics with lithium disilicate infrastructure-based (e.max HT and HO). The negative effects of increased opacity of the ceramic on the dual resin cement can be avoided with increased time of photoactivation.
Influence of different ceramic translucency on the degree of conversion and microhardness of dual resin cement
Keywords: materiais dentários; testes de dureza; cimentos de resina; dental materials; hardness tests; resin cements; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA